Impact of the Principle of Proportionality in Tax Law on the Jurisprudence of the Court of Justice of the European Union and the Supreme Administrative Court in Poland - Mudrecki, Artur (Public Governance, Administration and Finances Law Review, 2018)
The principle of proportionality in tax law as an EU and constitutional standard may play an important role in the interpretation of tax law. The principle of proportionality is associated with moderation of the activities of public authorities and minimization of their interference in the sphere of rights and freedoms. The principle of proportionality is also called the principle of commensurability, moderation, and adequacy. The article analyses the impact of the proportionality principle in tax law on the case law of the Court of Justice of the European Union. The case law of the Polish Supreme Administrative Court uses the principle of proportionality when interpreting tax law, and the judgments of the Court of Justice of the European Union and the Polish Constitutional Tribunal have a significant impact on the jurisprudence of administrative courts in Poland.